Near-complete chiral selection in rotational quantum states - JuHyeon Lee; Elahe Abdiha; Boris G. Sartakov; Gerard Meijer; Sandra Eibenberger-Arias (Nature Communications, 2024)
Abstract Controlling the internal quantum states of chiral molecules for a selected enantiomer has a wide range of fundamental applications from collision and reaction studies, quantum information to precision spectroscopy. Achieving full enantiomer-specific state transfer is a key requirement for such applications. Using tailored microwave fields, a chosen rotational state can be enriched for a selected enantiomer, even starting from a racemic mixture. This enables rapid switching between samples of different enantiomers in a given state, holding great promise, for instance, for measuring parity violation in chiral molecules. Although perfect state-specific enantiomeric enrichment is theoretically feasible, achieving the required experimental conditions seemed unrealistic. Here, we realize near-ideal conditions, overcoming both the limitations of thermal population and spatial degeneracy in rotational states. We achieve over 92% enantiomer-specific state transfer efficiency using enantiopure samples. This indicates that 96% state-specific enantiomeric purity can be obtained from a racemic mixture, in an approach that is universally applicable to all chiral molecules of C 1 symmetry. Our work integrates the control over internal quantum states with molecular chirality, thus expanding the field of state-selective molecular beams studies to include chiral research.